Shari'ah-compliant appraisal matrix for humanizing productivity for Islamic Higher Education Institutions: Sustainable Financial Management - Rosman, Romzie; Mohd Latiff, Nur Hanie; Amid, Azura (2021)
This is part of the Shari'ah-compliant appraisal matrix that focuses on the financial management of the Islamic Higher Education Institution that needs to be adopted.